Newly identified helper bacteria stimulate ectomycorrhizal formation in Populus - Labbé, Jessy L.; Weston, David J.; Dunkirk, Nora; Pelletier, Dale A.; Tuskan, Gerald A. (Frontiers in Plant Science, 2014)
Mycorrhiza helper bacteria (MHB) are known to increase host root colonization by mycorrhizal fungi but the molecular mechanisms and potential tripartite interactions are poorly understood. Through an effort to study Populus microbiome, we isolated 21 Pseudomonas strains from native Populus deltoides roots. These bacterial isolates were characterized and screened for MHB effectiveness on the Populus-Laccaria system. Two additional Pseudomonas strains (i.e., Pf-5 and BBc6R8) from existing collections were included for comparative purposes. We analyzed the effect of co-cultivation of these 23 individual Pseudomonas strains on Laccaria bicolor ‘S238N’ growth rate, mycelial architecture and transcriptional changes. Nineteen of the 23 Pseudomonas strains tested had positive effects on L. bicolor S238N growth, as well as on mycelial architecture, with strains GM41 and GM18 having the most significant effect. Four of seven L. bicolor reporter genes, Tra1, Tectonin2, Gcn5 and Cipc1, thought to be regulated during the interaction with MHB strain BBc6R8, were induced or repressed, while interacting with Pseudomonas strains GM17, GM33, GM41, GM48, Pf-5 and BBc6R8. Strain GM41 promoted the highest roots colonization across three Populus species but most notably in P. deltoides, which is otherwise poorly colonized by L. bicolor. Here we report novel MHB strains isolated from native Populus that improve L. bicolor root colonization on Populus. This tripartite relationship could be exploited for Populus species/genotypes nursery production as a means of improving establishment and survival in marginal lands.